Prof. Pierluigi Stefano: new options for the surgical treatment of aortic valve - Wang, Julia (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Prof. Stefano gave lectures in the Guangdong Provincial Cardiovascular Institute, Guangzhou in November 21st, 2017.